Carbon Emission Disclosure from a Legitimacy Perspective: Financial, Regulatory, and Environmental Dimensions - Evi Fauziah Rohmah; Henny Murtini (Universitas Pancasakti Tegal, 2026)
Research on carbon emission disclosure in Indonesia has predominantly focused on the corporate sector, despite the fact that responsibility for protecting the environment from carbon emissions is shared by all stakeholders. This study aims to examine the factors that influence carbon emission disclosure in local governments. The determinants of carbon emission disclosure consist of local government size, financial solvency, financial slack, local government regulation, environmental costs, and environmental performance. The sample selection method employed Isaac and Michael’s Table combined with a disproportionate stratified random sampling technique. The sample criteria included local governments located in regions that had experienced hydrometeorological disasters in 2024. A total of 228 samples were used. Multiple linear regression analysis was used to test the hypotheses. The results showed that local government size and local government regulation had a significant positive effect on carbon emission disclosure. Financial solvency, financial slack, and environmental performance had a significant negative effect on carbon emission disclosure, whereas environmental cost had no effect on carbon emission disclosure.